Testosterone dreams : rejuvenation, aphrodisia, doping - Hoberman, John M. (John Milton), 1944- (University of California Press, 2005)
"Testosterone Dreams is a detailed and frightening look at the shifting balance between patients' fantasies and the entrepreneurial bioscience that fuels these desires. Hoberman reveals the darker side of medicine that enhances athletic performances, and how the publicity given those performances generates wider demands for enhancement medicine. This book is a crucial contribution to the ethical deliberation of who we humans want to be, as bodies and as selves."--Arthur W. Frank, author of The Wounded Storyteller